"Reinhildis Has Died": Ascension and Enlivenment on a Twelfth-Century Tomb. Issue 1 (9th February 2015) - Fozi, Shirin
Abstract : From the time of their first appearance at the end of the eleventh century, medieval funerary effigies have presented their viewers with a strikingly uniform set of compositional conventions. The sculptural representation of the frontal body carved in relief on a rectangular slab is found so consistently among effigies of the twelfth through fifteenth centuries that this formula has become very nearly synonymous with the term "effigy" itself. The standard compositional type had already appeared in the bronze effigy of Rudolf of Swabia in Merseburg Cathedral (c.1080–1084), the earliest surviving effigy known to medieval art, and would be repeated for the tombs of the Nellenburg dukes of Schaffhausen (c.1105–1110), the Ottonian abbesses of Quedlinburg (c.1129), and the Merovingian kings from Saint-Germain-des-Prés in Paris (c.1150, now installed at Saint-Denis), to name just a few prominent examples. Each of these sculptures shows its subject dressed in different costume and holding different attributes as distinct signs of individual identity, but the representation of the frontal body remains a common, standardized feature of the group. Within this context, the twelfth-century effigy of Reinhildis of Riesenbeck (Fig. 1 )—twisting, turning, raising her hands in prayer, and gazing upward wide-eyed to witness the departure of her soul—stands out as an extraordinary exception to the general rule. No less startling than the visual enlivenment of the body is the dramatic textual content of its framing inscription, composed in rough Leonine hexameters:REINHELDIS OBI[TA] FVNDANT QVIQ[UE] PRECES—P[RO] VIRGINE QVE FVIT HERES PATRIS DEFVNCTI—GENITRIX QVAM SPONTE SECVNDI CONIVGIS OCCIDIT—MOX P[ER]CIPIENDO SVBIVIT SIDEREAS SEDES—CHRISTI PIA FACTA COHERES GERHARDVS [Reinhildis has died. Let everyone pour forth prayers for a virgin who was the heir of her deceased father; whom her mother murdered at the will of her second husband. At once she ascended, taking her place on the starry thrones, having become a blessed coheir of Christ. Gerhard.]